Quality Risk Management Framework: Guidance for Successful Implementation of Risk Management in Clinical Development. (January 2019) - Suprin, Melissa; Chow, Allan; Pillwein, Marion; Rowe, Jonathan; Ryan, Martin; Rygiel-Zbikowska, Beata; Wilson, Kevin Joseph; Tomlin, Irene
Effective quality risk management is fundamental to ensuring the protection of human subjects and reliability of clinical trial results during the conduct of clinical trials. Quality risk management supports effective delivery of clinical development programs and ultimately delivery of treatments to patients. Thus, risk management is a core element of an effective quality management system (QMS) as described in the TransCelerate Clinical Quality Management System (CQMS) conceptual framework. In addition, the landscape of quality risk management in clinical development evolves as regulatory authorities adopt elements of risk management to promote proactive quality management. This paper's goal is to provide a conceptual framework for quality risk management as part of a CQMS. The components of a quality risk management program are explored including foundational elements and quality risk management methods appropriate for clinical development.